SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA KARYAWAN DENGAN METODE ANALYTIC HIERARCHY PROCESS (AHP) - Zaenal Mustofa; Arsito Ari Kuncoro; Rizky Aji Prasetyo (STEKOM PRESS, 2020)
Decision Support System in Employee Performance Appraisal is a web-based system used to support decision making for outsourcing employee contract extensions. This study aims to provide a decision support information system in employee performance appraisal so that employee performance appraisals and employee contract extension decisions can be carried out systematically. Currently, employee performance appraisals and decision making for employee contract extensions are still done manually using spreadsheets. The method used in the design of decision support systems in the web-based employee performance appraisal is the method of calculating the assessment using the AHP (Analytic Hierarchy Process) method and the prototype system development method. The design of this system provides convenience to the personnel staff and the head of personnel in assessing and making decisions for employees who are about to expire their contract. The system can also be a means for personnel staff in accessing reports on employee data whose performance has been assessed by the division head and makes it easier for personnel staff to make decisions on employee contract extensions. With the system, employees will be more motivated to do their job better.